Religion and Post-Conflict Statebuilding - Dragovic, Denis. author. aut Link
XVII, 192 p.
Keywords: This book draws upon theory and theology to consider how religious institutions engage with post-conflict statebuilding and why they would choose to lend their resources to the endeavour. Drawing from the theologies of Roman Catholicism and Sunni Islam, Dragovic explores their possible motivations to engage alongside the international community.